Male mate choice in Allocosa alticeps (Araneae: Lycosidae), a sand-dwelling spider with sex role reversal - Aisenberg Olivera, Anita Diana (2011)
When males have high reproductive investment and female quality is variable, male assessment of sexual partners is expected. Allocosa alticeps (Mello-Leitão 1944) is a nocturnal wolf spider that shows a reversal in the sex roles and sexual size dimorphism usual in spiders. Females are the smaller, mobile sex, and they initiate courtship. Males construct burrows that serve as mating refuges and nests for female oviposition and cocoon care. In sex role reversed systems, male mate assessment is expected. Our objective was to test the occurrence of sequential male mate assessment based on female reproductive status and/or body characteristics in A. alticeps, discussing the results under sex role reversal hypotheses. We exposed males consecutively to virgin females and mated females and then recorded both courtship performance and mating occurrences relative to individuals' body characteristics. Virgin and mated females detected and entered male burrows in all the cases, and they were courted by males. However, copulations were more frequent with virgin females. The results suggest male mate selectivity in A. alticeps is based on female reproductive status. We discuss possible mechanisms underlying male mate choice in this species.